Predictors of Diarrhea after Hepatectomy and Its Impact on Gastrointestinal Quality of Life in Living Donors - Wang, Szu-Han (PLoS One, 2016)
BACKGROUND: Donor safety and preservation of donor health after living liver donation are of paramount importance. Diarrhea has a significant influence on gastrointestinal quality of life among donors who have undergone living donor hepatectomy. Thus, we aimed to investigate predictors of diarrhea after hepatectomy and its impact on gastrointestinal quality of life in living donors. METHODS: We retrospectively examined the medical records of 204 living liver donors who underwent hepatectomy during the period January 2010 to June 2013 at a single medical center. Diarrhea was defined as the passing of three or more liquid stools per day. The Chinese version of the Gastrointestinal Quality of Life Index (GIQLI) was used to assess the influence of diarrhea on quality of life in donors. RESULTS: During the study period, diarrhea was diagnosed in 62 (30.3%) of the 204 donors and the duration of diarrhea in the majority of them (n = 46, 74%) was <12 months. Risk factors associated with diarrhea included age [risk ratio (RR) = 0.84, 95% confidence interval (CI): 0.79–0.89, risk difference = 16%], and chronic cholecystitis (RR = 0.48, 95% CI: 0.24–0.99, risk difference = 52%). Compared to donors without diarrhea, donors with diarrhea had lower GIQLI scores in the following GIQLI domains: GI symptoms (1.8 vs. 3.6), physical function (2.1 vs. 3.5), emotional function (3.0 vs. 3.6), social function (3.3 vs. 3.7), and treatment reaction (2.6 vs. 3.7). CONCLUSIONS: Our findings show that younger donors and those without chronic cholecystitis are at increased risk for diarrhea after living donor hepatectomy and that diarrhea is associated with lower GIQLI scores after hepatectomy.